Persepsi Kafa’ah dalam Perkawinan menurut Masyarakat Petok Kec. Mojo Kab. Kediri Ditinjau dari Hukum Islam - Huzaimah Al-Anshori; Sholahudin Fathurrahman; Imam Makhali (Institut Agama Islam Negeri (IAIN) Kediri, 2020)
One of the steps to form compatibility in the family is mutual harmony or kafa’ah, a certain step to form a sakinah mawaddah wa rahmah family. The results of this study explain in the community of Petok Village, located in Mojo Subdistrict Kediri Regency, most of them really paying attention to and carry out kafa’ah in a marriage. In practice, there are those who prioritize kafa’ah in religion, however some people consider the concept of kafa’ah to be irrelevant, who rely on consensual elements as the basis for the marriages of their sons and daughters. A few of them put forward kafa’ah in terms of materials or prosperity. Most of the population of the Petok Village practice kafa’ah with one kufu in terms of religion, according to the madzabs of Malikiyah, Hanaafiyah, Shafi’iyah and Hanbaliyah, who agree that the implementation of kafa’ah is good. Meanwhile, the practice of kafa’ah in a small part of Petok villagers who emphasizes kufu in material / financial terms, according to the Malikiyah and Syafi’iyah, is not justified, while according to others, Hanafiyah and Hanbaliyah, it does not fulfill other kafa’ah elements. Thus, the implementing part of consensual is not found in the concept of kafa’ah in Islamic law.